Efektivitas Media Pembelajaran SMARTEVA dalam Pembelajaran IPA di Sekolah Menengah Pertama - Adekamisti, Revi; Candira WK, Dedi; Warsah, Idi; Wanto, Deri; Sholihin, Muhammad (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of the technology-based learning media, SmartEVA, in enhancing learning outcomes and student participation among ninth-grade students at SMPN 2 Kepahiang, Bengkulu. The background of this research centers on the challenges of digital-era learning, where students have diverse learning styles that are often not accommodated by conventional teaching methods. This study employed a quasi-experimental design involving a control group and an experimental group. The results indicate that students using SmartEVA showed significant improvements in both learning outcomes and participation. SmartEVA allows students to access materials according to their learning preferences (visual, auditory, or kinesthetic), which supports deeper material comprehension and active classroom participation. In conclusion, SmartEVA has proven effective in improving learning outcomes and participation among ninth-grade students at SMPN 2 Kepahiang, suggesting its potential for broader implementation to support technology-based learning in junior high schools.